The president's roles activities, and private office (1986-87): Patterns of practice and Management Principles - OCampo, Romeo B
Based largely on the empirical data derived from an organization and management study of the Office of the President conducted by the University of Philippines, College of Public Administration (UPCPA) in 1`987, the author describe the President's manifold roles time budget and the organisation and management of his/her office
Keywords: President; Powers and Functions; Presidents - Powers and Functions - Philippines